Niveles de proteína con suplementación de aminoácidos en la alimentación de pollos broilers - Hurtado Orellana, Marco Antonio (2011)
This study was conducted at the poultry farm "El Mirador" is located in the Km.1.5 a, 600 m. the right side of the road to San Carlos Quevedo, whose objectives are: a. To determine the effect of protein levels in the diet of broiler chickens supplemented with amino acids. b. Evaluate the performance parameters of birds, and c. Perform economic analysis of each of the treatments. We studied four levels of protein and aminoacid supplementation (DL-Methionine, L-Lysine and L-threonine) in the initial and final stage in the rearing of broilers in order to properly balance the requirements of the aforementioned amino acids is result of reduced protein. The treatments in the initial phase (0 to 28 days) were 21, 20.19 and 18% crude protein (CP), in the final phase (28 to 49 days) 19, 18.17 and 16% CP for T0, T1, T2 and T3 respectively. To which used 480 chicks from the Cobb 500 commercial line. We used a completely randomized design (CRD) with four treatments and six replicates. In addition, to determine the statistical differences between means were used Multiple Range Test of Tukey (P <0.05). With regard to weight gain in infancy, were statistically the same between the T0, T2 and T3 but there was statistical difference with the T1, the same that was in turn as the T0. In the final stage there were no statistical differences between treatments. Similarly in the total phase of the experiment also treatments were not statistically different (P <0.05). In the food consumption T0, T1 and T2 in the initial phase were not statistically different, but there were differences with the T3, the same which in turn was equal to the T2. Both the final phase as the total no statistical differences were found between treatments. With regard to feed conversion was not statistically different between treatments at any stage. As for the carcass yield was not statistical difference between treatments. With respect to mortality throughout the trial was 6.25% of which 96.6% was recorded in the final stage. From the results we can conclude: 1. Using 19 and 16% CP in the initial and final respectively, supplemented with amino acids in the diet of broiler chickens. respectively broilers. 2. Diets low in protein with amino acid supplementation can reduce feed costs 3. There was no statistical difference between treatments for carcass yield. 4. The T2 treatment had the highest benefit / cost ratio, because with this treatment is the best feed conversion reached the end of the experiment.